Investigation of dog ownership and physical activity on weekdays and weekends using longitudinal data from the SOEP Cohort - Yu TANIGUCHI; Tomoko IKEUCHI; Markus M. Grabka; Jongsay Yong (Scientific Reports)
Abstract This study examines the association between dog ownership over a period of 5 years (always, sometimes and no ownership) with physical activity on weekdays and weekends over a period of 6 years using the nationally representative German Socio-Economic Panel. Participants were asked if they had any pets and how many hours they spend on sports, fitness, and exercise. We hypothesized that the length of dog ownership may have different effects on the physical activity of the owner. Overall, 15,240 participants completed the questionnaire on dog ownership in both 2011 and 2016, and reported their physical activity levels at least once between 2013 and 2018. Generalized estimating equation models showed that, compared to no ownership, always dog ownership was associated with higher physical activity on weekdays (Coefficient = 0.106, Standard Error: SE = 0.027, P < 0.001) and weekends (Coefficient = 0.121, SE = 0.033, P < 0.001) respectively, after controlling for related socio-demographic, physical, and psychological factors during the 6-year follow-up period. During the same follow-up period, sometimes dog ownership had no clear association with physical activity on both weekdays (Coefficient=-0.012, SE = 0.033, P = 0.706) and weekends (Coefficient = 0.049, SE = 0.039, P = 0.209) compared to no ownership. This study showed for the first time that longer dog ownership is associated with higher physical activity on both weekdays and weekends. Future research will be needed to investigate whether any causal relationships underlie the association.